Comercialização de madeira serrada de florestas naturais em Mato Grosso : um diagnóstico do setor de base florestal - Ribeiro, Edilene Silva (2013)
This study aimed to characterize the forest-based sector in the state of Mato Grosso for the period 2004 to 2010, identifying tree species, measuring the quantity (m³) and values of timber sold and analyzing the municipalities of origin lumber and destination states such timber. To this end, we proceeded qualitative and quantitative diagnosis of forestry in the state, showing the challenges, barriers and potential forest. The collection was performed using the database of the Institute of Agricultural Protection in the State of Mato Grosso (INDEA) (origin, destination, municipalities and species), through the Secretary of State for the Environment (SEMA) through SISFLORA (GF3), and also the Secretary of Treasury of the State of Mato Grosso by normative act 106/2012 establishing the registry where the list of minimum prices for products from the forest industry and vegetal extraction. Then the qualitative analyzes were expressed in literature reviews (jobs, industries and GDP) and quantitative data expressed and analyzed through graphs and tables for Microsoft Excel Software. The first chapter deals with the identification of forest species commercialized and the real amounts of this marketing. We identified 411 forest species, distributed in 97 genera and 34 plant families. The species most traded in terms of volume of wood were Qualea sp (27%), Goupia glabra (16%), Erisma uncinatum (13%) and Mezilaurus itauba (11%). The period of data collection was seven years in which the state had revenues in current values of R $ 5,411,524,557.24. The second chapter aims to analyze which municipalities and suppliers of lumber sales volume in the period 2004 to 2010. Of the 141 municipalities in the state 61.7% participated as a source of origin of timber sold, with a total traded volume of 7,385,350.46 m³. The third chapter aimed to identify the regions of origin and final destination of the timber sold. The state of Mato Grosso in seven years with sold wood twenty states of the federation, especially São Paulo, Santa Catarina, Paraná, Rio Grande do Sul, Rio de Janeiro, Mato Grosso do Sul and Minas Gerais were the biggest consumers. The state of Mato Grosso continued trade with all regions of Brazil, and South and Southeast consumed more than 92.42% of timber sold.